THE IMPACT OF FACILITIES AND SERVICE QUALITY ON PRIVATE HOSPITAL CLIENTS’ SATISFACTION - Iswati, Iswati; Qomariah, Siti Nur; Kadir, Khairul Azmi Abd (DIVERSITY Logic Journal Multidisciplinary, 2025)
Background. Market rivalry is getting fiercer both at the domestic level and internationally. As a result, many private hospitals based on hospital business companies compete with one another to win over clients by establishing objectives like offering first-rate facilities and customer service. Research Purpose. Determining the impact of facilities and service quality on private hospital clients’ satisfaction was the aim of this study. Research Method. This study uses quantitative statistics as its methodology, gathering data via documentation, questionnaire distribution, and observation. The Accidental Sampling approach was used by the author to sample the population. In this study, 80 respondents made up the sample. Data quality testing, multiple linear regression analysis, hypothesis testing, partial and simultaneous determination coefficient testing, and the classical assumption test are the methods of data analysis that are employed. Findings. Customer satisfaction is significantly impacted by both service quality (p=0.000) and facility factor. Additionally, customer happiness is significantly impacted by both facility factors and service quality. Conclusion. Client happiness is significantly impacted by service quality, facility concerns, and changeable facilities.